2021
DOI: 10.1038/s41533-021-00221-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic obstructive pulmonary disease and ventricular arrhythmia: a nationwide population-based cohort study

Abstract: The ventricular arrhythmia (VA)–chronic obstructive pulmonary disease (COPD) association and related risk factors remain unclear. Using 2001–2012 data from National Health Insurance Research Database, we retrospectively reviewed 71,838 patients diagnosed as having COPD and 71,838 age- and sex-matched controls. After adjustments for comorbidities, medication, urbanization level, and monthly income, patients with COPD had higher incidence rates of VA than did the controls (adjusted hazard ratio [aHR] [95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Kong ( 29 ) indicated this association based on heart rate deceleration runs. Chen ( 31 ) manifested the age- and sex-specific association of COPD with VA development. Kusunoki ( 7 ) points out that increased VA is likely related to the peculiar pathophysiology of COPD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kong ( 29 ) indicated this association based on heart rate deceleration runs. Chen ( 31 ) manifested the age- and sex-specific association of COPD with VA development. Kusunoki ( 7 ) points out that increased VA is likely related to the peculiar pathophysiology of COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Salpetera et al noted that a single, regular dose of inhalation of salbutamol enhances atrioventricular nodal conduction and shortens the atrial refractory period, thereby increasing the incidence of arrhythmias ( 48 ). However, Chen et al ( 31 ) reported that the combination of short-acting Beta2 agonists and short-acting muscarinic agonists helped reduce VA risk. Since available data could not draw a unanimous conclusion, a more detailed, larger sample study was expected to conduct for investigating a better treatment in COPD patients with arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is associated with a twofold to threefold increased risk of having cardiovascular disease (CVD), independent of age, sex, smoking history or other confounders, 4 and CVD contributes significantly to the burden of disease in people living with COPD. [4][5][6][7][8] Hence, the importance of identifying and…”
Section: Introductionmentioning
confidence: 99%
“…The disease may also involve acute worsening of symptoms, referred to as COPD exacerbation. COPD is associated with a twofold to threefold increased risk of having cardiovascular disease (CVD), independent of age, sex, smoking history or other confounders,4 and CVD contributes significantly to the burden of disease in people living with COPD 4–8. Hence, the importance of identifying and monitoring cardiopulmonary risk factors or CVD in patients with COPD is increasingly emphasised 9 10…”
Section: Introductionmentioning
confidence: 99%
“…164 МЕДИЦИНСКИЙ СОВЕТ 2022;16(4): [163][164][165][166][167][168] Диссертант ВВЕДЕНИЕ На сегодняшний день внимание специалистов все больше привлекает проблема коморбидности, изучение которой позволяет реализовать персонализированный подход к ведению пациентов [1][2][3]. В частности, бронхообструктивные заболевания тесно связаны с патологией сердечно-сосудистой системы [4]. Растущая распространенность астмы в последнее десятилетие становится все более серьезной проблемой здравоохранения [5,6].…”
unclassified